1989
DOI: 10.1111/j.1439-0310.1989.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Cues Used by Hatchling Loggerhead Sea Turtles (Caretta caretta L.) During their Offshore Migration

Abstract: Sea turtle hatchlings ernerge from underground nests, crawl to the ocean and swim out to sea. The orientation cues used to maintain offshore headings are unknown. Our field experiments suggest loggerhead hatchlings on the Atlantic coast of Florida continue on offshore headings by swimming into oceanic swells and wind‐generated waves. Dependence on these cues appears complete when hatchlings are 3.0 km from shore. Because waves and swells usually approach from seaward directions, they are generally reliable gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“… 1 Williams , 2 Masclaux et al , 3 Prospero , 4 Mahowald et al , 5 Shi et al , 6 Hajrasuliha et al , 7 Bai et al , 8 Chaiwanakupt and Robertson , 9 Webster et al , 10 Stephens et al , 11 Cothran et al , 12 Junker and Cross , 13 Minakawa and Gara , 14 Sullivan et al , 15 Waters , 16 Brittain and Eikeland , 17 Cross et al , 18 Cross et al , 19 Veldboom and Haro , 20 Petrone et al , 21 McDowell and Sharpley , 22 Wolanski et al , 23 Coale et al , 24 Slomp and Van Cappellen , 25 de Baar et al , 26 Sterner et al , 27 Elser and Hassett , 28 Royer et al , 29 Falkowski et al , 30 Hopkinson et al , 31 Salmon and Lohmann , 32 Salmon et al , 33 Bouchard and Bjorndal , 34 Müller , 35 Griffith et al , 36 Muehlbauer et al , 37 Veldboom and Haro , 38 Heywood , 39 Kohler et al , 40 Jonsson and Jonsson , 41 Rüegg et al , 42 Helfield and Naiman , 43 Chaloner et al , 44 Tiegs et al , 45 Mobæk et al , 46 Geremia et al , 47 Thomas et al , 48 Senft et al , 49 Ruess and McNaughton , 50 Van Uytvanck et al , 51 Sitters et al , 52 Kitchell et al , 53 Gauthier et al , 54 Liu et al , 55 Weimerskirch et al , 56 Ballance et al , 57 Wakefield et al , 58 Maron et al .…”
Section: Impacts Of Spatial and Temporal Scales On The Stoichiometry mentioning
confidence: 99%
“… 1 Williams , 2 Masclaux et al , 3 Prospero , 4 Mahowald et al , 5 Shi et al , 6 Hajrasuliha et al , 7 Bai et al , 8 Chaiwanakupt and Robertson , 9 Webster et al , 10 Stephens et al , 11 Cothran et al , 12 Junker and Cross , 13 Minakawa and Gara , 14 Sullivan et al , 15 Waters , 16 Brittain and Eikeland , 17 Cross et al , 18 Cross et al , 19 Veldboom and Haro , 20 Petrone et al , 21 McDowell and Sharpley , 22 Wolanski et al , 23 Coale et al , 24 Slomp and Van Cappellen , 25 de Baar et al , 26 Sterner et al , 27 Elser and Hassett , 28 Royer et al , 29 Falkowski et al , 30 Hopkinson et al , 31 Salmon and Lohmann , 32 Salmon et al , 33 Bouchard and Bjorndal , 34 Müller , 35 Griffith et al , 36 Muehlbauer et al , 37 Veldboom and Haro , 38 Heywood , 39 Kohler et al , 40 Jonsson and Jonsson , 41 Rüegg et al , 42 Helfield and Naiman , 43 Chaloner et al , 44 Tiegs et al , 45 Mobæk et al , 46 Geremia et al , 47 Thomas et al , 48 Senft et al , 49 Ruess and McNaughton , 50 Van Uytvanck et al , 51 Sitters et al , 52 Kitchell et al , 53 Gauthier et al , 54 Liu et al , 55 Weimerskirch et al , 56 Ballance et al , 57 Wakefield et al , 58 Maron et al .…”
Section: Impacts Of Spatial and Temporal Scales On The Stoichiometry mentioning
confidence: 99%
“…three grid cells) are assumed to be within the area swum by hatchlings during their first 24 h at sea (Salmon and Wyneken, 1987;Witherington, 2002). It is acknowledged that research on the east coast of the USA has demonstrated that marine turtle hatchlings use wave cues for a relatively short period of the swimming frenzy before switching to a magnetic compass (Salmon and Lohmann, 1989;Lohmann and Lohmann, 1992). However, wind speed and direction calculated across the three grid cells (12 km) represent near-shore coastal conditions relevant to hatchling dispersal.…”
Section: Sea Turtle Nesting Sitesmentioning
confidence: 99%
“…We therefore used a second behavioural assay to determine whether turtles in both groups could respond appropriately to non-magnetic cues. Previous work has demonstrated that hatchlings swim directly into waves when they leave the beach, a response that guides turtles away from shore and towards the open ocean [22][23][24][25]. Additionally, turtles determine wave vertical coil power supply horizontal coil power supply cable from digital encoder computer Figure 2.…”
Section: (E) Wave Orientation Testsmentioning
confidence: 99%